The Relationship Between Clean Water Sanitation And Maternal Behavior Towards The Incidence Of Diarrhea In Toddlers At The Lahusa Health Center, Lahusa District, South Nias Regency In 2020 - Meiyati Simatupang; Della Winda Gultom; Jonni Silaban (Science Midwifery, 2020)
Diarrheal disease is still one of the main causes of pain and death, especially in toddlers. Some of the most dominant factors that cause diarrhea are the means of providing clean water and fecal discharge, where these two factors can interact with human behavior. This research is a quantitative study with a cross-sectional study design. The sample in this study was toddlers aged 10-59 months, totaling 90 respondents. The data used in this study are secondary data from related agencies and primary data obtained through interviews and observations. From the results of the study, 35.6% had diarrhea and 64.4% did not have diarrhea. Then from the bivariate results with a α of 5% two variables were obtained related to the incidence of diarrhea in toddlers, namely the use of a latrine with a p-value of 0.024 and the habit of washing hands p-value 0.050. Meanwhile, the variables of clean water sanitation facilities (pv 0.082) and cooking water (pv 1,000) have no meaningful relationship with diarrhea. Suggestions that can be given are to increase public knowledge about diarrheal diseases by conducting counseling related to diarrhea and PHBS, as well as increasing cooperation and communication between the puskesmas and the community so that it is easier for the public to get information about the importance of health.